Anti-LGI1 autoimmune limbic encephalitis: an easy-to-miss diagnosis - Carolina Freitas Henriques; Rui Fernandes; Leonor Neves; Rubina Miranda; Duarte Noronha; Teresa Carolina Aguiar; Teresa Faria (European Journal of Case Reports in Internal Medicine)
Background: Autoimmune limbic encephalitis (ALE) is a rare inflammatory disorder characterised by a subacute onset, usually within weeks. The presence of multiple neuropsychiatric symptoms such as seizures, short-term memory deficits, anxiety and depression often leads to misdiagnosis as another medical condition, contributing to poor prognosis and reduced long-term survival. Case description: A 60-year-old man, with no chronic illnesses, presented at the emergency department with daily episodes of palpitations, shivering, piloerection and a sense of impending doom lasting two months. Initially diagnosed with anxiety disorder and treated with venlafaxine 50 mg daily, he showed no improvement and developed memory loss. Hospitalised three months later, he exhibited both temporal and spatial disorientation, along with short-term memory loss. Key findings included elevated serum sedimentation rate, hyponatraemia, increased cerebrospinal fluid (CSF) protein levels and cranial magnetic resonance imaging evidence of bilateral temporal intra-parenchymal lesions, suggesting limbic encephalitis. After ruling out alternative diagnoses, screening of autoantibodies in the CSF was requested, which was positive for anti-LGI1 antibodies. The diagnosis of anti-LGI1 ALE was assumed, and treatment was initiated with significant clinical and imaging improvement. Conclusions: ALE’s broad clinical spectrum contributes to underdiagnosis. Therefore, in patients with new onset of neuropsychiatric symptoms and no prior psychiatric history, ALE should be considered, as prompt diagnosis and treatment are pivotal to achieve a good prognosis.